An unexpected copper-catalyzed carbonylative acetylation of amines. Issue 1 (8th December 2016) - Li, Yahui; Wang, Changsheng; Zhu, Fengxiang; Wang, Zechao; François Soulé, Jean; Dixneuf, Pierre H.; Wu, Xiao-Feng
Abstract : A novel copper-catalyzed carbonylative acetylation of amines has been developed. Abstract : A novel copper-catalyzed carbonylative acetylation of amines has been developed. With peroxide as the oxidant as well as the methyl source with a copper catalyst under CO pressure, good yields of N -acetyl amides could be obtained. Notably, this is the first example of carbonylative acetylation.